Persuasive communication model of the â€œSatuan Gugus Tugasâ€ Pandemic (A case study of the â€œSATGAS COVID-19â€ in Yogyakarta) - Kusuma, Alan; Lestari, Puji; Sosiawan, Edwi Arief (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
The Yogyakarta government established the COVID-19 Task Force, involving various organizations, to effectively communicate with the public during the pandemic. Employing a persuasive communication model, the task force integrates the heart communication theory and utilizes techniques such as association, participation, and fear arousal. The study aims to identify this persuasive communication model's effectiveness for pandemic control. Utilizing a qualitative approach and case study methodology on the Yogyakarta COVID-19 Task Force, data collection involved interviews, observations, and documentation. The results reveal a hub-patterned organizational communication model, centered around the head of the COVID-19 Task Force, facilitating coordination. Techniques like association, participation, and fear arousal are applied to persuade the public to adhere to health protocols. Additionally, the task force incorporates the heart communication theory among field teams to manage emotions, fostering sympathy and empathy for disaster-affected populations. This approach ensures cautious communication to prevent conflicts within the community, contributing valuable insights for future disaster management strategies. This article contributes a tailored persuasive communication model for the COVID-19 Task Force, offering practical insights into effective strategies, emotional intelligence integration, and organizational communication. The focus on Yogyakarta's local context enhances the relevance of the findings, serving as a valuable resource for policymakers and disaster management teams in shaping future communication strategies.